Conservation of Medicinal Plants : Conventional and Contemporary Strategies, Regulations and Executions - Sajwan, Bikram Singh; Chandra Prakash, Kala (Indian Forester, 2007)
The philosophy of use and conservation of medicinal plants has evolved with the social and cultural groupings of human beings. At present, there are many international and national treaties and laws pertaining to the conservation and management of medicinal plants. Internationally, the Convention on Biological Diversity and the Convention on International Trade in Endangered Species of Wild Fauna and Flora are the two major treaties and India is one of the signatories of both the treaties. At the national level in India, there are many Acts and regulations, Indian Forest Act 1927, Wildlife (Protection) Act 1972, Forest (Conservation) Act 1980 and Biological Diversity Act 2002, for instance. These Acts enable to conserve and regulate the over-exploitation of valuable biodiversity including the rare and endangered species of medicinal values. Besides, the creation of the National Medicinal Plants Board has accelerated and given impetus to sustainable utilization of medicinal plants across the country. The present article discusses the major strategies and policies related to the conservation and management of the medicinal plants.